Outdoor Sportsmanship - Forest, Christopher (The Child's World, 2024)
"Explores important principles of sportsmanship that any outdoor enthusiast should know when hunting or fishing, including guidelines for respecting both fellow hunters and anglers, as well as the environment. Additional features include a table of contents, sidebars, infographics, Fast Facts, critical thinking questions, a phonetic glossary, an index, and sources for further research"--
Grades 4-6